Kepemimpinan Kolaboratif - Ella Lemanawati Wargadinata (Institut Pemerintahan Dalam Negeri (IPDN), 2016)
The shifting on public administration on theoretical or conceptual framework is influencing the public administration directly on empirical practices. The terms of bureaucracy, privatization, governance, coordination and collaboration are reflecting its progressiveness and those applied on day to day governmental actions. Collaborative governance has emerged as a response to the failures of the public organization monopoly on public services delivery. Instead of governance context, the concept of collaborative leadership captures the key element to articulate and discover win-win solutions among stakeholders.